An Experimental Study on the Simultaneous Phenol and Chromium Removal From Water Using Titanium Dioxide Photocatalyst - Elaheh Faghih Nasiri; Daryoush Yousefi Kebria; Farhad Qaderi (Civil Engineering Journal, 2018)
Organic pollutants along with heavy metals and organic metal compounds may cause abnormal changes in physical and chemical parameters (acidity, alkalinity, salinity, color, smell and taste) of aquatic ecosystems and are among the serious threats of environmental health, especially the water resources. In this study, the effect of titanium dioxide photocatalyst with different concentrations (50, 100, 200, 500 and 1000 mg/l) on the simultaneous removal of phenol and heavy metal (chromium) from aqueous solution of the closed system was investigated.  In order to determine the optimal concentrations of photocatalyst, all the tests were conducted in pH =7, using ultraviolet light with 100 watt power. The highest rate of phenol and chromium removal was observed at concentration of 100 mg/ml which was equal to 72.3% and 67.2%, respectively. Study of the reaction kinetics showed that the reactions of phenol and chromium removal were zero and first-order, respectively.